The University Teacher and his World: A Sociological and Educational Study - Richard Startup (Saxon House, 1979)
The aim of this work is to analyse the occupational role of the university teacher, with the help of data collected within a specific university institution. This involves examining both what is expected of university teachers and what they actually do, and accounting for the patterns which their activities exhibit. Since the university teacher's occupation is muliti-faceted it is necessary to examine several areas of activity including teaching, research and 'external' professional activities, as well as a number of types of relationships in which lecturers are involved. Data is presented and interpreted from interviews with the staff of four selected departments of a British provincial university (classics, pure mathematics, civil engineering and psychology) and also from questionnaire surveys of staff and students. Sociologically the university may be regarded as an organisation or institution, and the behaviour of its members understood through the notion of 'social role'. On the educational side of the study the central concern is with the teacher-pupil relationship. We are also confronted with a basic human problem of how employed people weave elements to give meaning to their working lives.